Psoriasis Area and Severity Index response in moderate‐severe psoriatic patients switched to adalimumab: results from the OPPSA study. (1st June 2018) - Talamonti, M.; Galluzzo, M.; Bernardini, N.; Caldarola, G.; Persechino, S.; Cantoresi, F.; Egan, C.G.; Potenza, C.; Peris, K.; Bianchi, L.
Abstract: Background: Few studies have compared the efficacy of switching to adalimumab in the real‐life setting in plaque psoriasis patients. Objective: To evaluate the effect of adalimumab in psoriasis patients previously treated with other biologics. Methods: In this multicentre study, psoriasis patients ( N  = 262) treated with an anti‐TNF‐alpha agent, ustekinumab or naïve to biologics then switched to adalimumab were included. Disease severity was assessed by the Psoriasis Area and Severity Index (PASI) at baseline and after 3, 6, 12, 24 and 36 months. The association between clinical risk factors and achievement of PASI response was evaluated by logistic regression. Results: Adalimumab treatment resulted in a decrease in PASI (15.1 ± 6.2 at baseline vs. 2.7 ± 4.8 at 6 months, P  < 0.0001), regardless of previous biologic treatment. Furthermore, adalimumab allowed 92.5%, 79% and 56% of patients to achieve PASI response (PASI 50, 75 and 90, respectively) and complete remission (PASI 100 response) in 48.4% of patients, by 6 months and maintained over 3 years, independent of prior biologic treatment. The absence of metabolic syndrome, dyslipidemia, hypertension and lower PASI and lower age at baseline was associated with achievement of PASI response at 3, 6 and 12 months, whereas at later time points (24 and 36 months), PASI 90 and PASI 100 response was associated with diagnosis of psoriasis/psoriatic arthritis. Conclusion: Adalimumab was effective at reducing PASI score over 3 years, irrespective of whether patients were biologic naïve or previously treated with a TNF‐alpha or IL‐12/23 inhibitor.